2012
DOI: 10.2298/bah1204689b
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of dairy farm structure and characteristics of dairy production systems in Serbia

Abstract: In order to have a more precise description of dairy farm structure and characteristics of dairy production systems, as well as to assess possibilities for improving production and farming conditions in which milk production is organized, a survey based research was directed at a select group of farms across the Serbia. 1180 questionnaires have been mailed to farmers whose farms are registered for either cattle or mixed production. Questionnaire was divided into 6 sections: general information of the farm, agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
2
0
3
Order By: Relevance
“…While the majority of the enterprises produce their own roughage (91.2%), the percentage of farmers who prefer to buy was determined as 8.8% (Figure 2a). Similarly, it was reported by several researchers that cattle enterprises in the Narman county of Erzurum (Diler et al, 2018), in Muş province (Bakır and Kibar, 2018), in Kars Province (Demir et al,2013), in Serbia (Bogdanović et al, 2012) and in the USA (Dou et al, 2001) produced mostly their own roughage. In contrast, percents of the enterprises purchased roughage from other farms in Hınıs county of Erzurum Province, in Bingöl, in Kahramanmaraş were 63.0% (Diler et al (2016), 88.7% (Daş et al, 2014) and 61.0% (Kaygısız and Tümer, 2009).…”
Section: Sources Of Roughage and Concentrate Feed Supplysupporting
confidence: 52%
See 1 more Smart Citation
“…While the majority of the enterprises produce their own roughage (91.2%), the percentage of farmers who prefer to buy was determined as 8.8% (Figure 2a). Similarly, it was reported by several researchers that cattle enterprises in the Narman county of Erzurum (Diler et al, 2018), in Muş province (Bakır and Kibar, 2018), in Kars Province (Demir et al,2013), in Serbia (Bogdanović et al, 2012) and in the USA (Dou et al, 2001) produced mostly their own roughage. In contrast, percents of the enterprises purchased roughage from other farms in Hınıs county of Erzurum Province, in Bingöl, in Kahramanmaraş were 63.0% (Diler et al (2016), 88.7% (Daş et al, 2014) and 61.0% (Kaygısız and Tümer, 2009).…”
Section: Sources Of Roughage and Concentrate Feed Supplysupporting
confidence: 52%
“…The rate of enterprises that purchased concentrate feed was 32.7%, while the percentage of the enterprises which used rental lands for production was 1.3% (Figure 2b). Similarly, Dou et al (2001), Önal and Özder (2008), Bogdanović et al (2012), and Tilki et al (2013) stated that concentrate feed was mostly produced in the enterprises. On the other hand, Kılıç and Eryılmaz (2020), Bakır and Kibar (2018), Diler et al (2016), Daş et al (2014) and Kaygısız and Tümer (2009) reported that concentrated feed used in the cattle farms was mostly purchased from out of the enterprises.…”
Section: Sources Of Roughage and Concentrate Feed Supplymentioning
confidence: 95%
“…Türkiye'de yapılan diğer çalışmalar da saman kullanımının yaygın olduğu ve genellikle ilk sırayı aldığı bildirilmiştir (Özyürek ve ark., 2014;Budağ ve Keçeci, 2013;Bakır ve Demirel, 2001). Bunun aksine Bogdanović et al (2012) Sırbistan'da süt sığırcılığı yapan işletmelerin kaba yem olarak kuru çayır otu, kuru yonca ve mısır silajı kullandıklarını bildirmişlerdir. Bu araştırmada elde edilen saman kullanım oranı diğer yapılan çalışmalardan daha düşük oranda bulunmuştur.…”
Section: Kaba Ve Kesif Yem Teminiunclassified
“…Benzer şekildeDemir ve ark. (2013) Kars ilinde,Bogdanović et al (2012) Sırbistan'da veDou et al (2001) ABD'de işletmelerin kaba yemin büyük oranda kendi üretimleri olduklarını bildirmişlerdir. Bunun aksine Diler ve ark.…”
unclassified
“…Percentage of those who produced concentrate feeds in their own enterprises was also determined as 19% by . Kaygısız and Tümer (2009) and Daş et al (2014) stated that concentrate feed is mostly acquired from outside the farm, while Dou et al (2001), Önal and Özder (2008), Bogdanovic et al (2012) and Tilki et al (2013) was indicated that the majority of concentrate feed is met from within the enterprise. On the other hand, Soyak et al (2007) and Sezer et al (2020) found out respectively that 65% and 69.5% of breeders purchased the concentrate feeds from local feed dealers.…”
Section: Sources Of Roughage and Concentrate Feed Supplymentioning
confidence: 99%